2021
DOI: 10.7759/cureus.13258
|View full text |Cite
|
Sign up to set email alerts
|

Will Protective Innovations Like the “Airway Box” Become Routine Practice After the Pandemic?: An Opinion Survey

Abstract: Background Tracheal intubation carries an elevated risk of exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) due to the generation of aerosols containing high concentrations of the virus. An airway box was designed to mitigate the exposure of healthcare professionals performing intubations. Aim We evaluated usability and sustainability in the routine practice of the "airway box" as a protective device during high-risk airway procedures. Materials and methods After institutional review bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Additionally, the structured qualitative evaluation conducted through the use of a questionnaire identifies specific concerns based on direct provider experience. Interestingly, a study by Ellison et al, which evaluated the use of an aerosol box in clinical use for emergent intubations, reported that the majority of practitioners who used the device found it easy to use, although it was rarely used despite being a readily available option [20].…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Additionally, the structured qualitative evaluation conducted through the use of a questionnaire identifies specific concerns based on direct provider experience. Interestingly, a study by Ellison et al, which evaluated the use of an aerosol box in clinical use for emergent intubations, reported that the majority of practitioners who used the device found it easy to use, although it was rarely used despite being a readily available option [20].…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…The aerosol box was designed to mitigate HCP infection by providing a physical barrier to minimize exposure to aerosols . This study showed that aerosol box use reduces surface contamination on the PPE (torso and face) of airway practitioners after performing AGMPs.…”
Section: Discussionmentioning
confidence: 97%
“…The aerosol box has been implemented by some hospitals worldwide for management of COVID-19 patients who are critically ill . Studies demonstrate that aerosol box use potentially reduces spread of aerosolized particles, but is often associated with technical challenges .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in emergency and intensive care, these procedures are often essential for patient treatment and survival, and any delay in their implementation would be a detriment to the patients. Since the beginning of the COVID-19 pandemic, there have been many reports of the use of aerosol boxes, with the aim being to reduce aerosol dispersion, thereby preventing secondary infections among HCPs [2][3][4].…”
Section: Introductionmentioning
confidence: 99%